Kinship, Expectations, and God - Hershkovits, Keren Abbou (Hawwa, 2017)
The conquest of the Middle East by Muslims ultimately resulted in the Islamization of the region. The long process by which this took place awaits clarification. Conversion narratives, permitting us a glimpse into relations between Muslims, non-Muslims, and converts, might serve to elucidate this process. This study examines how different families responded to religious conversion within their ranks. It will show that in early Islam, individuals moved between different spheres, all the while negotiating their roles and commitments. Rather than considering the act of conversion itself, this study engages with the range of responses generated by conversion that were recorded by medieval historians, biographers, and ḥadīth collectors. The present contribution seeks to demonstrate, through anecdotes of conversion, the ways in which kinship ties functioned in the face of shifts in personal status. I also hope to show that boundaries between religious communities (to the extent that they indeed existed) were much more porous, or perceived as such, than has been previously thought. The anecdotes concern the early days of Islam among pagans and shed light on communities’ reception or rejection of Muḥammad’s call.